Structural analysis of automotive cowl parts considering welding residual stress - Bang, Hee-Seon; Park, Chang-Soo; Bang, Han-Sur (International journal of precision engineering and manufacturing, 2017)
Recently the automotive industry has been focusing on the development of eco-friendly cars with improved fuel efficiency and lower CO 2 emission such as hybrid vehicles, in order to reduce environmental pollution. Many are also carrying out research on laser stitch welding, rather than the usual spot welding, to manufacture high quality automobiles as well as to improve the general productivity. The main advantages of laser stitch welding include weight lightening by minimizing flange size, improved strength of welded joints and the ability to adapt to complicated shapes. Therefore, in this study, numerical analysis has been carried out to realize design optimization and secure the reliability of automotive cowl parts assembled by the laser stitch welding process. For this, the residual stress production mechanism in laser stitch welded joints of automotive cowl parts, has been investigated and compared with that of spot welded joints. Moreover, structural analysis of automotive cowl parts considering welding residual stress with welding methods has been carried out.